Straddling the Personal and the Academic: How Self in Academic Writing is Constructed in Contact Zone - Sugiharto, Setiono (UNIB Press, 2024)
Drawing on the notion of the contact zone (Pratt, 1991), this qualitative case study investigates the construction of self in the academic writing of three Indonesian novice writers. Its aims are twofold: (a) to explore how students constructed self in academic writing, including the way they negotiated tensions between their expectations and their teachers, as well as the challenges posed to their writing self in the presence of the dominant discourse, and (b) to identify possible rhetorical postures of their texts. Data were obtained via writing conferences, field notes, and participant observations and analyzed using thematic coding. Results show that the self was constructed by (a) venerating established authorities, (b) depersonalizing knowledge, (c) personalizing knowledge, and (d) through discursivity and linearity. As for the rhetorical postures, different constructions of self in writing yield different rhetorical postures, which can be classified as either discordant or coherent potential. This study concludes that the self as the aspect of identity is invariably unstable, ambivalent, and even conflictual, as it always undergoes changes over time motivated by the dynamics of social contexts of writing. So construed, writing can no longer be treated as a value-free and autonomous activity devoid of one’s values, preferential biases, beliefs, and allegiances to realities.